Comparative Effectiveness of Second-Line Targeted Therapies for Metastatic Renal Cell Carcinoma: A Systematic Review and Meta-Analysis of Real-World Observational Studies. - Daniel Y Heng; James Signorovitch; Elyse Swallow; Nanxin Li; Yichen Zhong; Paige Qin; Daisy Y Zhuo; Xufang Wang; Jinhee Park; Sotirios Stergiopoulos; Christian Kollmannsberger (PLoS ONE)
Objective The optimal sequencing of targeted therapies for metastatic renal cell carcinoma (mRCC) is unknown. Observational studies with a variety of designs have reported differing results. The objective of this study is to systematically summarize and interpret the published real-world evidence comparing sequential treatment for mRCC. Methods A search was conducted in Medline and Embase (2009-2013), and conference proceedings from American Society of Clinical Oncology (ASCO), ASCO Genitourinary Cancers Symposium (ASCO-GU), and European Society for Medical Oncology (ESMO) (2011-2013). We systematically reviewed observational studies comparing second-line mRCC treatment with mammalian target of rapamycin inhibitors (mTORi) versus vascular endothelial growth factor (VEGF) tyrosine kinase inhibitors (TKI). Studies were evaluated for 1) use of a retrospective cohort design after initiation of second-line therapy, 2) adjustment for patient characteristics, and 3) use of data from multiple centers. Meta-analyses were conducted for comparisons of overall survival (OS) and progression-free survival (PFS). Results Ten studies reported OS and exhibited significant heterogeneity in estimated second-line treatment effects (I2 = 68%; P = 0.001). Four of these were adjusted, multicenter, retrospective cohort studies, and these showed no evidence of heterogeneity (I2 = 0%; P = 0.61) and a significant association between second-line mTORi (>75% everolimus) and longer OS compared to VEGF TKI (>60% sorafenib) (HR = 0.82, 95% CI: 0.68 to 0.98) in a meta-analysis. Seven studies comparing PFS showed significant heterogeneity overall and among the adjusted, multicenter, retrospective cohort studies. Real-world observational data for axitinib outcomes was limited at the time of this study. Conclusions Real-world studies employed different designs and reported heterogeneous results comparing the effectiveness of second-line mTORi and VEGF TKI in the treatment of mRCC. Within the subset of adjusted, multicenter observational studies, second-line use of mTORi was associated with significantly prolonged survival compared with second-line use of VEGF TKI.